Rapid effective dose calculation for raster-scanning 4He ion therapy with the modified microdosimetric kinetic model (mMKM) - Kopp, Benedikt; Mein, Stewart; Tessonnier, Thomas; Besuglow, Judith; Harrabi, Semi B.; Heim, Eric; Abdollahi, Amir; Haberer, Thomas; Debus, Jürgen; Mairani, Andrea (Physica medica, 2021)
Purpose - To develop and verify effective dose (DRBE) calculation in 4He ion beam therapy based on the modified microdosimetric kinetic model (mMKM) and evaluate the bio-sensitivity of mMKM-based plans to clinical parameters using a fast analytical dose engine. - Methods - Mixed radiation field particle spectra (MRFS) databases have been generated with Monte-Carlo (MC) simulations for 4He-ion beams. Relative biological effectiveness (RBE) and DRBE calculation using MRFS were established within a fast analytical engine. Spread-out Bragg-Peaks (SOBPs) in water were optimized for two dose levels and two tissue types with photon linear-quadratic model parameters αph, βph, and (α/β)ph to verify MRFS-derived database implementation against computations with MC-generated mixed-field α and β databases. Bio-sensitivity of the SOBPs was investigated by varying absolute values of βph, while keeping (α/β)ph constant. Additionally, dose, dose-averaged linear energy transfer, and bio-sensitivity were investigated for two patient cases. - Results - Using MRFS-derived databases, dose differences ≲2% in the plateau and SOBP are observed compared to computations with MC-generated databases. Bio-sensitivity studies show larger deviations when altering the absolute βph value, with maximum D50% changes of ~5%, with similar results for patient cases. Bio-sensitivity analysis indicates a greater impact on DRBE varying (α/β)ph than βph in mMKM. - Conclusions - The MRSF approach yielded negligible differences in the target and small differences in the plateau compared to MC-generated databases. The presented analyses provide guidance for proper implementation of RBE-weighted 4He ion dose prescription and planning with mMKM. The MRFS-DRBE calculation approach using mMKM will be implemented in a clinical treatment planning system.
Im Titel ist die Zahl 4 hochgestellt
Gesehen am 09.04.2021